2022
DOI: 10.1021/jacs.1c12934
|View full text |Cite
|
Sign up to set email alerts
|

On the Origin of Rh-Catalyzed Selective Ring-Opening Amidation of Substituted Cyclopropanols to Access β2-Amino Ketones

Abstract: β2-Amino carbonyls, an α-substituted β-amino scaffold, hold a prominent place in the development of new pharmaceuticals and peptidomimetics. Herein, we report a highly efficient Rh-catalyzed ring-opening amidation of substituted cyclopropanols, which turned out to serve as a linchpin for the selective synthesis of β2-amino ketones to outcompete the formation of β3-isomers. Instead of the generally accepted rationale to consider steric factors for the β2-selectivity, orbital interaction was elucidated to play a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 103 publications
0
23
0
Order By: Relevance
“…Experimental procedures and characterization data and copies of 1 H NMR and 13 C NMR spectra for all new compounds (PDF)…”
Section: ■ Associated Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental procedures and characterization data and copies of 1 H NMR and 13 C NMR spectra for all new compounds (PDF)…”
Section: ■ Associated Contentmentioning
confidence: 99%
“…Cyclopropanols, easily accessible compounds with intrinsic strain property, are often regarded as an important class of homoenolate equivalent, which can intercept with various electrophiles to forge different functional groups at the β-position of carbonyl compounds . Pioneered by seminal works developed by Nakamura and Kuwajima using siloxycyclopropanes as the homoenolate precursor to participate in diverse addition and cross-coupling reactions mediated by metal salts, numerous ring-opening cross-coupling reactions of cyclopropanol by transition metals have been devoted to access a variety of functionalities at the β-position of ketone moiety. The existing protocols mainly focus on the intramolecular cycloisomerization or two-component cross-coupling (Scheme i, a). Despite the sustainable advances, the multicomponent reaction of the cyclopropanol is underdeveloped.…”
mentioning
confidence: 99%
“…While further applications had been obstructed mainly due to the often unavoidable Curtius-type decomposition, the Bolm group later revitalized this chemistry by the development of an elegant alternative system merging Ru catalysis and photoirradiation . These seminal findings inspired others, including our group, for the advancements relying on transition-metal catalysis, which have subsequently built a new synthetic paradigm to enable unorthodox amidation transformations.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Bolm et al reported a light-induced ruthenium-catalyzed synthesis of N -acyl sulfoximines and sulfimides via a ruthenium N -acyl nitrene intermediate using dioxazolone . Following a preliminary observation of metal nitrenoid intermediate, dioxazolones have been widely investigated in reactions involving the formation of new C–N bonds that are catalyzed by transition metals such as Fe, Rh, Co, Ir, and Ru, and these reactions have been used in the construction of acyclic and cyclic amides such as β- and γ-lactams and β-amido ketone scaffolds . Although dioxazolones have demonstrated significant potential in the field of metal-catalyzed C–H activation, further studies on reactions involving C–N bond formation using 3d transition metals are still needed.…”
mentioning
confidence: 99%